Menjaga Warisan Keislaman: Peran Madrasah Ibtidaiyah dalam Menyebarkan Nilai-Nilai Agama Islam di Kalangan Pendidikan Jenjang Dasar - Munawir (Risâlah Jurnal Pendidikan dan Studi Islam, 2026)
Islamic heritage is a valuable asset for Muslims that needs to be maintained and preserved. Madrasah Ibtidaiyah, as an Islamic elementary educational institution, has an important role in spreading Islamic values to the younger generation. This study aims to analyze the role of Madrasah Ibtidaiyah in spreading Islamic values among elementary education levels. This study uses a qualitative approach, with a library research design of books, the latest journals and other sources of information that support the writing of this article. The results show that Madrasah Ibtidaiyah has an important role in spreading Islamic values among elementary education levels. This role is realized through the curriculum, learning activities, and character development.